Fatigue and Fracture of Fibre Metal Laminates - Alderliesten, René (Solid Mechanics and Its Applications,, 2017)
This book contributes to the field of hybrid technology, describing the current state of knowledge concerning the hybrid material concept of laminated metallic and composite sheets for primary aeronautical structural applications. It is the only book to date on fatigue and fracture of fibre metal laminates (FMLs). The first section of the book provides a general background of the FML technology, highlighting the major FML types developed and studied over the past decades in conjunction with an overview of industrial developments based on filed patents. In turn, the second section discusses the mechanical response to quasi-static loading, together with the fracture phenomena during quasi-static and cyclic loading. To consider the durability aspects related to strength justification and certification of primary aircraft structures, the third section discusses thermal aspects related to FMLs and their mechanical response to various environmental and acoustic conditions.